PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) BERORIENTASI KECAKAPAN HIDUP (LIFE SKILL) PADA MATERI SISTEM REPRODUKSI MANUSIA - AMELIA PUTRI, VINDA (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
Learning based on life skills need to be taught to students in order to form an independent and creative person. The purpose of this study are 1) generates life skills worksheets in the reproductive system material viable in terms of content, language and appearance, 2) describe the rational skills and social skills of students, 3) improve student learning outcomes by using design "Shot case study", 4) describe the student's response. This research is development with the Research & Development model of Borg and Gall modification by Sukmadinata stages: 1) a preliminary study, 2) the development stage, 3) limited testing phase in XI Science 4 class SMAN 3 Mojokerto. The results of life skills worksheets study get an average score of 3.88 and 3.95 with good criteria. Rational skills get score of 4 and 3, while the social skills of students getting score 4 and 3.67 with very well criteria. Completeness student learning outcomes by 86% (13 students who completed and 2 students who have not completed). Completeness of learning objectives by 87% (8 learning objectives complete and 1 learning objectives which not yet complete) and positive student response with score 87% gain the answer "yes" to life skills worksheets. Based on the conclution of this resume that the development of life skills worksheets for use in learning both theoretically and empirically, and completed the learning outcomes of students and also received a good response from the students. Keywords: Worksheets Development, Life Skills, Human Reproductive System.